Microplastics in the endangered Indo-Pacific humpback dolphins (Sousa chinensis) from the Pearl River Estuary, China. (1st February 2021) - Zhang, Xiyang; Luo, Dingyu; Yu, Ri-Qing; Xie, Zhenhui; He, Lei; Wu, Yuping
Abstract: Microplastic pollution is a growing concern worldwide. Despite numerous studies showing the occurrence of microplastics in low-trophic level aquatic organisms, microplastic ingestion and contamination in cetaceans, especially those from Asian waters, has been rarely recorded. Here, we investigated stomach microplastic pollution in twelve Indo-Pacific humpback dolphins stranded along the Pearl River Estuary (PRE), China. We also compared microplastic abundances in dolphins stranded near populated urban areas (ZH, n = 6) with those stranded near rural areas (JM, n = 6). Microplastics were detected in all samples, with abundance ranging widely from 11 to 145 items individual −1 (mean ± SD, 53 ± 35.2). Major microplastics were polypropylene and polyethylene fibers, with the size mostly ranging from 1 to 5 mm and the dominant colors of white or transparent. Humpback dolphins from ZH (73 ± 36.8 items individual −1 ) exhibited a significantly higher average microplastic abundance than those from JM (33 ± 18.3 items individual −1, p < 0.05). In particular, the highest microplastic concentration was identified in the dolphin (SC-ZH01) stranded near the mouth of the Pearl River, whereas the dolphin (SC-JM04) collected at the rural site contained the lowest concentration of microplastics, suggesting the important influence of land-based human activities on the accumulation of microplastics in the PRE. The identification of varied microplastic polymers indicated their complex source scenarios. This study suggests that, as one of top predators in the potential microplastic food chains, this cetacean species could likely serve as an endpoint biomonitoring species of microplastic pollution in the PRE or other similar estuarine ecosystems. Our results highlight the need for more studies towards better understanding the potential impacts of microplastics on this endangered species. Graphical abstract: Image 1 Highlights: Microplastics were first reported to appear in Indo-Pacific humpback dolphins from the PRE. Dolphins near urban areas contained significantly more microplastics than those near rural areas. Microplastics were predominantly fiber-shaped, white, and composed of polypropylene. The humpback dolphin could serve as a biomonitoring species for microplastic pollution in the PRE. Abstract : Abundance, physicochemical characteristics, and spatial patterns of microplastics were reported, for the first time, in Indo-Pacific humpback dolphins from the Pearl River Estuary (PRE). The Indo-Pacific humpback dolphin could be a potential biomonitor for microplastic pollution in the PRE.